2022
DOI: 10.3389/fnbeh.2022.846315
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of Loneliness, Isolation, and Loss: Integrating Human and Animal Perspectives

Abstract: In social species such as humans, non-human primates, and even many rodent species, social interaction and the maintenance of social bonds are necessary for mental and physical health and wellbeing. In humans, perceived isolation, or loneliness, is not only characterized by physical isolation from peers or loved ones, but also involves negative perceptions about social interactions and connectedness that reinforce the feelings of isolation and anxiety. As a complex behavioral state, it is no surprise that lone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 289 publications
2
25
0
Order By: Relevance
“…In other words, the network can be more responsive, i.e., requires lower levels of input to activate, in mothers with improved social cognition. Consistent with our other analyses, mothers show a more responsive limbic network which supports their responsiveness to affective stimuli that underlie self-referential and other-referential action 33,72,73 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In other words, the network can be more responsive, i.e., requires lower levels of input to activate, in mothers with improved social cognition. Consistent with our other analyses, mothers show a more responsive limbic network which supports their responsiveness to affective stimuli that underlie self-referential and other-referential action 33,72,73 .…”
Section: Discussionsupporting
confidence: 89%
“…Mothers with higher social cognition scores had decreased inhibition from the amygdala to the parahippocampal gyrus, and from the parahippocampal gyrus to the nucleus accumbens, relative to non-mothers. The nucleus accumbens-amygdala-parahippocampal gyrus network forms the affective limbic network that is implicated in social connectedness, and its converse, loneliness 72 . This network overlaps with the subcortical components of the ventromedial emotion regulatory system, which is implicated in early appraisal, encoding, and automatic regulation of emotion 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the chronic stress of loneliness might lead to poor metabolic and mental health through numerous pathways—including dysregulation of sympathoadrenal or autonomic nervous system function [for reference, see Vitale and Smith ( 20 )]—evidence for the effect of loneliness on these systems remains relatively scant and inconsistent ( 21 ). Here, we focus on the overactivation of the hypothalamic-pituitary-adrenal (HPA) axis and its downstream immunometabolic consequences, particularly as they relate to mitochondrial function dysregulation.…”
Section: Loneliness Leads To Pathophysiological Changes: a Chronic St...mentioning
confidence: 99%
“…An integrated review based on human and animal neurobiological studies concluded that social support could help protect against neurological dysfunction [8]. Social support is defined as the availability of assistance from others in times of need or crisis, including emotional, instrumental, informational and companionship support [9,10].…”
Section: Introductionmentioning
confidence: 99%